Solid phase extraction using nylon membranes with fluorescence detection as a fast and sensitive method for Amiloride and Furosemide determination in urine samples - Peralta, Cecilia Mariana (2011)
A diuretic is a substance widely prohibited in competition sports, by the World Anti-Doping Agency (WADA). In this paper, a sensitive, rapid and convenient analytical solid phase extraction-fluorimetric method for the determination of furosemide (FUR) and amiloride hydrochloride (AMI) diuretics in human urine was developed. FUR and AMI exhibit overlapped fluorescent spectra and urine produces background fluorescence that precludes the direct determination of these diuretics by conventional fluorimetry. AMI was adsorbed using nylon membranes whereas; FUR was detected in aqueous solutions. The optimum analytical conditions for AMI and FUR assay were established. Excitation wavelengths of 365nm and 237nm and emission wavelengths of 406 and 415nm were used for AMI and FUR, respectively. The calibration graphs are linear in the range of 3.7×10-4 to 0.8 μgmL-1 and 1.2×10-3 to 4.0 μgmL-1, for AMI and FUR, respectively, with a detection limit of 1.1×10-4 and 3.5×10-4μgmL-1 (S/N=3). These concentrations correspond well with the range of the drugs in urine. AMI and FUR were accurately quantified in doped urine samples and urine of subjects under medical treatment with diuretic. The results were validated by recovery test, being highly satisfactory.